PEMBANGUNAN PLTMH RANTEBALLA DI KABUPATEN LUWUK, SULAWESI SELATAN SEBAGAI PROYEK PENGURANGAN EMISI RUMAH KACA, - Irhan Febijanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Renewable energy fuelled power generations are not many developed by privatesector in Indonesia. The incentive provided by Indonesia government is not enough to encourage private sector to develop renewable energy fuelled power generation. Credit carbon as an additional revenue from Clean Development Mechanism is utilized in Ranteballa Hydro Power Plan development. This project contributes to reduce green effect gas generated in South Sulawesi grid system. This paper describes the calculation of emission reduction generated from the Ranteballa Hydro Power development, and also the evaluation regarding emission carbon produced in the recent five years. BPPT has a role of CDM facilitator in this project development, and has a collaboration with CDM in vestor, Chugoku Electric Power and the owner of the project PT Fajar Futura Energi Luwu. Key words : green house gasses, global warming, hydro power, emission factor, emissionreduction, electricity